Body size rather than reflectivity explains thermal constraints on colour variation in an aposematic jewel bug - Kei-Lin M. Ooi; Iliana Medina; Fabian C. Salgado-Roa; Devi Stuart-Fox (Evolutionary Ecology, 2025)
Theory posits that warning signals should converge phenotypically to reinforce predator memory, yet many aposematic species show substantial variation in warning signals within and between populations. This could be explained by alternative selective pressures on phenotype beyond predation such as thermoregulation, but empirical tests are scarce and do not consider the full spectrum of sunlight. To examine whether trade-offs with thermoregulation could explain variation in warning colouration, we examined thermal properties of colour variants of the aposematic cotton harlequin bug ( Tectocoris diophthalmus ). This species shows striking variation in warning signals: it is sexually dichromatic, varies within sexes, and shows clinal variation in colour frequencies, with iridescent blue-green colouration prevalent in cooler climates and non-iridescent red–orange colouration prevalent in warmer climates. We quantified reflectivity between colour variants over the full solar spectrum and investigated the contribution of ultraviolet and visible (UV–visible, 300–700 nm) and near infrared (NIR, 700–1700 nm) light on heating. Differences in reflectivity of iridescent and non-iridescent colour patches were greater in NIR than UV–visible wavelengths but did not result in significant differences in heating. However, we found a tight link between body size and reflectivity, with smaller males having lower reflectivity and heating faster. Due to the strong correlation between body size and colouration, thermal constraints related to body size may help to explain the observed clinal variation in colour frequencies.

Disentangling thermal from alternative drivers of reflectance in jewel beetles: A macroecological study - Lu‐Yi Wang; Amanda M. Franklin; Andrew F. Hugall; Iliana Medina; Devi Stuart‐Fox (Global Ecology and Biogeography, 2023)
Aim To predict future colour–climate relationships, it is important to distinguish thermal drivers of reflectance from other evolutionary drivers. We aimed to achieve this by comparing relationships between climate and coloration in ultraviolet–visible (UV–Vis) and near‐infrared (NIR) light, separately. Location Samples were distributed primarily across Australia and North America, with some from Africa and Asia. Major taxa studied Coleoptera: Buprestidae. Methods We used jewel beetles as models to identify climatic drivers of reflectance, because jewel beetles have highly diverse coloration and a wide distribution and are often active in hot conditions. Specifically, we tested the association between climate, body size and reflectance using a phylogenetic comparative analysis for three wavebands (UV–Vis, NIR and total). Results Reflectance of jewel beetles was more strongly predicted by body size than by climate. NIR reflectance and total reflectance were not associated with climate, but larger beetles had higher NIR reflectance. For UV–Vis reflectance, small beetles were darker in warmer and more humid environments, whereas there was no association with climate for large beetles. Main conclusions Our study suggests that variation in reflectance of jewel beetles is not driven by thermal requirements and highlights the importance of considering NIR reflectance when evaluating explanations of the effects of colour on thermoregulation.

Shouting the odds: vocalization signals status in a lizard - Toby J. Hibbitts; Martin J. Whiting; Devi M. Stuart-Fox (Behavioral Ecology and Sociobiology, 2007)